The Influence Of Science Dichotomy On Islamic Religious Education Curriculum - Wahyu Aji; Ziyah; Mahwiyah (Penerbit Hellow Pustaka, 2023)
Islamic religious education is defined as a conscious effort to prepare students to believe, understand, live, and practice the Islamic religion through activities, guidance, teaching, and training by taking into account the demands to respect other religions and relations between religious communities in society in order to realize national unity. Integrated Islamic Education is an alternative to overcome the occurrence of educational dichotomy. But this Integrated Islamic education can be carried out with the condition that the two existing education systems in Muslim countries can be merged into one system, as long as the philosophical basis remains Islamic. The style of integrated Islamic education is the integration or combination of various existing education systems, without the dichotomy of religious knowledge and general science. So that it can give birth to an education system that is inspired by Islam. Islam has never considered the dichotomy of science and religion. Science and religion are an integral totality that cannot be separated from one another.